1999
DOI: 10.2525/ecb1963.37.143
|View full text |Cite
|
Sign up to set email alerts
|

Water and Nitrogen Effects on the Growth and Yield of Spring Wheat.

Abstract: To study the combined effects of controlled water and nitrogen supplies on growth and yield of spring wheat (Triticum aestivum L.), plants were grown in a controlled environment chamber during the entire growth period.When the 3rd leaf was visible, three levels each of water and nitrogen supply, for a total of nine treatments, were applied using the system to accurately control soil water and nitrogen levels. There was a significant interaction of water and nitrogen levels on growth and yield of wheat. Under l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The PPFD effects on LWP were accelerated under severe water stress and water supply effects on them were also accelerated under higher PPFDs. Tamaki et al (1999) also showed that water deficiency lowered LWP in the other study.…”
Section: And Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The PPFD effects on LWP were accelerated under severe water stress and water supply effects on them were also accelerated under higher PPFDs. Tamaki et al (1999) also showed that water deficiency lowered LWP in the other study.…”
Section: And Discussionsupporting
confidence: 56%
“…Roy and Gallagher (1985) and Davidson and Chevalier (1987) observed that drought delayed tiller emergence. Krenzer et al (1991) and Tamaki et al (1999) also found lower leaf emergence rates at low water supply.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations